2022
DOI: 10.3390/genes13081410
|View full text |Cite
|
Sign up to set email alerts
|

Determining Genetic Diversity and Population Structure of Common Bean (Phaseolus vulgaris L.) Landraces from Türkiye Using SSR Markers

Abstract: Assessment of genetic diversity among different varieties helps to improve desired characteristics of crops, including disease resistance, early maturity, high yield, and resistance to drought. Molecular markers are one of the most effective tools for discovering genetic diversity that can increase reproductive efficiency. Simple sequence repeats (SSRs), which are codominant markers, are preferred for the determination of genetic diversity because they are highly polymorphic, multi-allelic, highly reproducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 55 publications
(81 reference statements)
2
9
0
Order By: Relevance
“…Genetic diversity indices of lupin, based on SNPs, is high among the nine populations sampled across the Peruvian Andes, which is concordant for individuals that are landraces, as reported for other landraces of rye [51], pea [52] , maize [53], rice [54,55], squash [56], bean [57], wheat [58]. The wealth and abundance among tarwi landraces can be explained due to their adaptation to local environments and diversity of grower´s choice [49].…”
Section: Discussionsupporting
confidence: 68%
“…Genetic diversity indices of lupin, based on SNPs, is high among the nine populations sampled across the Peruvian Andes, which is concordant for individuals that are landraces, as reported for other landraces of rye [51], pea [52] , maize [53], rice [54,55], squash [56], bean [57], wheat [58]. The wealth and abundance among tarwi landraces can be explained due to their adaptation to local environments and diversity of grower´s choice [49].…”
Section: Discussionsupporting
confidence: 68%
“…Türkiye's historical position at the crossroads of the Palearctic region, both culturally and geographically, makes it potentially influential in the dissemination of common bean genotypes from Asia to Europe and Africa. Although Türkiye is not recognized as the primary origin or center of domestication for the common bean, the previous studies indicated a wide diversity in common bean germplasm from Türkiye (Nadeem et al, 2018;Haliloğlu et al, 2022;Özkan et al, 2022;Yeken et al, 2022). These studies revealed that the common landrace collection in Türkiye harbored a substantial amount of genetic diversity.…”
Section: Introductionmentioning
confidence: 93%
“…SSR molecular marker technology involves tandem repeat sequence consisting of 1–6 nucleotides as repeat units, which has excellent characteristics such as co-dominant inheritance, high polymorphism, good reproducibility, and stable and accurate results. It has emerged as a key molecular marker technology for plant genetic diversity analysis, population structure research, variety identification, and molecular ID construction [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%